To cooperate or compete? Looking at the climate change issue in the wine industry. Issue 3 (17th August 2015) - Galbreath, Jeremy
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to explore the nature of the cooperation–competition nexus in regional clusters by examining how wine firms in Australia engage in knowledge exchanges about a "common" strategic issue: climate change. Further, it determines if differences in climate change innovations exist based on sub-regional position. Design/methodology/approach – Using a survey, data were collected from 557 firms across three wine-producing regions in Australia. Respondents were drawn from a leading wine industry database. Findings – The findings suggest that, after accounting for all knowledge exchanges, firms across the regions appear to be generally engaging in knowledge exchanges about climate change within their own geographic sub-regions. However, paradoxically, firms in "elite" sub-regions appear to be demonstrating more of a cooperative posture via a greater level of external knowledge exchanges. The results also suggest that implementation rates differ for adaptive climate change innovations only (as opposed to mitigative innovations) to the apparent advantage of firms in elite sub-regions. Research limitations/implications – The study represents Australian wine regions and should not be taken as a general population sample. The impacts of climate change in other wine-producing regions around the world may vary, leading to different results than those found in this study. Practical implications – Wine producers face many challenges with respect to climate change. To respond effectively to this issue, the sharing of knowledge is important to innovate around mitigative and adaptive practices. This research suggests that greater stimulation of open knowledge exchanges is likely needed so that all producers can benefit from industry-wide learning. Originality/value – This paper provides insights to wine scholars, industry practitioners and peak industry bodies seeking to understand and enhance the wine industry's response to climate change. The paper also points to areas of future research opportunity and provides policy recommendations.